Cover Feature: An Exceptionally Efficient Co−Co2P@N, P‐Codoped Carbon Hybrid Catalyst for Visible Light‐Driven CO2‐to‐CO Conversion (Chem. Eur. J. 34/2018). Issue 34 (7th June 2018) - Xu, Yong; Mo, Jiang; Fu, Zi‐Cheng; Liu, Su; Yang, Zhi; Fu, Wen‐Fu
Abstract : A visible light‐driven system for CO2 ‐to‐CO conversion, which consists of a heterogeneous hybrid catalyst of Co and Co2 P nanoparticles embedded in carbon nanolayers codoped with N and P (Co‐Co2 P@NPC) and a homogeneous Ru II ‐based complex photosensitizer, was established. It was shown that the exceptional catalytic activity in CO2 photoreduction was due to the nanoparticle size, the partially adsorbed H2 O molecules on the catalyst surface, and the hybrid nature of the systems. More information can be found in the Full Paper by W.‐F. Fu et al. onpage 8596 .